2003
DOI: 10.1590/s1677-55382003000300004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic investigation of patients with urolithiasis in a specific region

Abstract: Objective: To assess the prevalence of the main metabolic alterations found in patients with recent diagnosis of urolithiasis in the West region of Paraná state, Brazil.Materials and Methods: We made a retrospective study on 425 patients with evidence of recent formation of renal stones. Laboratory assessment consisted in 3 samples of 24-hour urine with dosing of calcium, uric acid, citrate, oxalate, sodium and creatinine. A urine culture was also made and qualitative cystinuria and urinary pH following 12-hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…Cystinuria is an autosomal recessive disorder affecting 1% of adults and 10% of children with kidney stones. In Brazil, screening for this disorder is usually done with sodium nitroprusside 5,6 . The test is considered positive when the concentration of cystine in the urine is above 100mg/L 14 .…”
Section: Morphological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Cystinuria is an autosomal recessive disorder affecting 1% of adults and 10% of children with kidney stones. In Brazil, screening for this disorder is usually done with sodium nitroprusside 5,6 . The test is considered positive when the concentration of cystine in the urine is above 100mg/L 14 .…”
Section: Morphological Analysismentioning
confidence: 99%
“…The main related metabolic changes observed are hypercalciuria, hyperoxaluria, hyperuricosuria, hypocitraturia and hypomagnesiuria [4][5][6] . These metabolic disorders are risk factors for lithiasis, but may occur in patients who never develop kidney stones.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, hypercalciuria was the prevalent metabolic change. In the West of Paraná, the ingestion of milk and dairy products is not expressive; meanwhile, the ingestion of salt and protein is frequent, which probably contributes to the occurrence of hypercalciuria 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalciuria, hyperuricosuria, hypocitraturia, hyperoxaluria, cystinuria and urinary infection are the main causes of calculus formation 9,10 .…”
Section: Nephrolithiasismentioning
confidence: 99%
“…However, these disorders are not routinely investigated in these patients, and its frequency varies widely according to ethnical and environmental factors. Different studies of metabolic assessment in patients with urinary lithiasis have reported a high incidence of metabolic disorders as a causal factor (3,4). Recently, Akagashi and others (5) evaluated 82 Japanese patients with staghorn calculus and found the following metabolic alterations: hypercalciuria in 37.8% and cistinuria in 2.4%.…”
Section: Commentsmentioning
confidence: 99%